(untitled) (Baghdad Science Journal, 2012)
Leucine aminopepotidase (LAP)[EC:3.4.11.1] activity has been assayed in (50) serum samples of patients with diabeties naphrophathy D.N (non-insulin dependent diabetic (NIDD) , and (50)serum sample of healthy individuals without any clinically detectable diseases have been as control group. The aim of this study is to measure leucine aminopeptidase activity and partially purifying the enzyme from sera of patients with diabetes nephropathy The results of this study revealed that Leucine aminopeptidase (LAP) activity of nephropathy patient’s serum shows a high signifiacant increase (p < 0.001) compared to that of the healthy subjects.LAP was purified from the serum of patients with diabetes nephropathy by dialysis and gel filtration (Sephadex G-25) (fine ) (20 × 1.5 cm ) .A (1.37) fold purification of serum LAP from patients serum with diabetic nephropathy was achieved by using dialysis and this enzyme showed single grade increased to (8.33) fold by using gel filtration Abbreviation: Leucine aminopeptidase=LAP, Diabetes Nephropathy= D.N, Non- Insulin dependent diabetic= NIDD.